Mechanical Support in Early Cardiogenic Shock: What Is the Role of Intra-aortic Balloon Counterpulsation? - Kimman, Jesse R. (Curr Heart Fail Rep, 2020)
PURPOSE OF REVIEW: We aim to summarize recent insights and provide an up-to-date overview on the role of intra-aortic balloon pump (IABP) counterpulsation in cardiogenic shock (CS). RECENT FINDINGS: In the largest randomized controlled trial (RCT) of patients with CS after acute myocardial infarction (AMICS), IABP did not lower mortality. However, recent data suggest a role for IABP in patients who have persistent ischemia after revascularization. Moreover, in the growing population of CS not caused by acute coronary syndrome (ACS), multiple retrospective studies and one small RCT report on significant hemodynamic improvement following (early) initiation of IABP support, which allowed bridging of most patients to recovery or definitive therapies like heart transplant or a left ventricular assist device (LVAD). SUMMARY: Routine use of IABP in patients with AMICS is not recommended, but many patients with CS either from ischemic or non-ischemic cause may benefit from IABP at least for hemodynamic improvement in the short term. There is a need for a larger RCT regarding the role of IABP in selected patients with ACS, as well as in patients with non-ACS CS.